Cesar Chavez: A Hero for Everyone - Soto, Gary (Simon & Schuster, Inc., 2003)
Up and down the San Joaquin Valley of Califonia, and across the country, people chanted these words. Cesar Chavez, a migrant worker himself, was helping Mexican Americans work together for better wages, for better working conditions, for better lives. No one thought they could win against the rich and powerful growers. But Cesar was out to prove them wrong- and that he did.
Keywords: Juvenile Non-Fiction/ Biographies